MPS 18-01 MODE OF ACTION OF RB150, AN AMINOPEPTIDASE A INHIBITOR PRODRUG AS A CENTRALLY-ACTING ANTIHYPERTENSIVE AGENT IN DOCA-SALT HYPERTENSIVE RATS. (September 2016) - Hmazzou, Réda; Flahault, Adrien; Marc, Yannick; Llorens-Cortes, Catherine
Abstract : Objective: In the brain, angiotensin III (AngIII) generated from angiotensin II (AngII) by aminopeptidase A (APA) exerts a tonic stimulatory action on the control of blood pressure (BP) in hypertensive rats. Inhibition of brain APA by RB150, an orally active prodrug of the specific and selective APA inhibitor, blocks brain AngIII formation and normalizes BP in hypertensive rats. Since following blockade of brain AngIII formation by RB150, no AngII accumulation was observed, we aimed to delineate if this treatment induces the activation of another metabolic pathway of brain AngII, in particular angiotensin converting enzyme type 2 (ACE2) which converts AngII into angiotensin 1–7 (Ang1–7). Design and Method: For this purpose, RB150 and MLN4760, an ACE2 inhibitor, were administered by intracerebroventricular (ICV) route after insertion of an intracerebral cannula to alert DOCA-salt rats, a model of salt-dependent hypertension. Mean arterial blood pressure (MABP) was recorded via an arterial femoral catheter. Maximal MABP decrease and area under the curve (AUC) of the variations in MABP were calculated. Results: ICV administration of RB150 (100 μg) significantly decreased MABP compared to vehicle (−23 ± 3 mmHg vs −6 ± 2 mmHg; AUC: 17.6 ± 2 vs 2.1 ± 3). Administration of MLN4760 (10 μg) didn't induce any significant change of MABP compared to vehicle (−10 ± 3 mmHg; AUC: 1.4 ± 2). Co-administration of MLN4760 (10 μg) with RB150 (100 μg) partially inhibits RB150-induced BP decrease. Conclusions: In conclusion, ICV administration of the ACE2 inhibitor alone has no effect on BP indicating that in DOCA-salt rats, brain Ang1–7 does not exert a tonic stimulatory effect on the control of BP. However, when conversion of brain AngII into AngIII is blocked by RB150, there is an activation of the conversion by ACE2 of brain AngII into Ang1–7, which by acting on the Mas receptor, may participate to the RB150-induced BP decrease in hypertensive rats.